Evidence of phylosymbiosis in Formica ants - Jackson, Raphaella; Patapiou, Patapios A.; Golding, Gemma; Helanterä, Heikki; Economou, Chloe K.; Chapuisat, Michel; Henry, Lee M. (Frontiers in Microbiology, 2023)
Insects share intimate relationships with microbes that play important roles in their biology. Yet our understanding of how host-bound microbial communities assemble and perpetuate over evolutionary time is limited. Ants host a wide range of microbes with diverse functions and are an emerging model for studying the evolution of insect microbiomes. Here, we ask whether phylogenetically related ant species have formed distinct and stable microbiomes. To answer this question, we investigated the microbial communities associated with queens of 14 Formica species from five clades, using deep coverage 16S rRNA amplicon sequencing. We reveal that Formica species and clades harbour highly defined microbial communities that are dominated by four bacteria genera: Wolbachia, Lactobacillus, Liliensternia, and Spiroplasma. Our analysis reveals that the composition of Formica microbiomes mirrors the phylogeny of the host, i.e. phylosymbiosis, in that related hosts harbour more similar microbial communities. Our analysis also revealed significant correlations between microbe co-occurrences, which suggests that synergistic and antagonistic interactions may contribute to the phylosymbiotic signal. Additional factors potentially contributing to the phylosymbiotic signal are discussed, including host phylogenetic relatedness, host-microbe genetic compatibility, modes of transmission, and similarities in host ecologies (e.g., diets). Overall, our results support the growing body of evidence that microbial community composition closely depends on the phylogeny of their hosts, despite bacteria having diverse modes of transmission and localisation within the host.